2004
DOI: 10.1080/00365590410033443
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Polymorphism in 385 Patients on Renal Replacement Therapy in Sweden

Abstract: In this study, variations in the frequencies of the apo epsilon4 allele and the apo E3/E4 and E4/E4 genotypes were found in patients with NIDDM, GN and ADPKD. This result may be a consequence of the effects of the apo epsilon4 and epsilon2 alleles on P-cholesterol and remnant lipoprotein levels. The decreased frequency of apo E3/E4 found in patients with NIDDM may be explained by the fact that the epsilon4 allele gives renoprotection against diabetic nephropathy by lowering plasma remnant lipoprotein levels. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…For example, a study by Roussos et al (2004) also suggested the involvement of APOE in renal disease but in their study the implicated allele was APOE3E4 genotype in a subgroup of ESRD patients with NIDDM; however, they did not observe a higher percentage of APOE2 in their cases, compared to controls. Other studies failed to detect any significant differences in APOE genotypes between patients with kidney disease and controls (Feussner et al 1992, Guz et al 2000, Arikan et al 2007).…”
Section: Resultsmentioning
confidence: 90%
“…For example, a study by Roussos et al (2004) also suggested the involvement of APOE in renal disease but in their study the implicated allele was APOE3E4 genotype in a subgroup of ESRD patients with NIDDM; however, they did not observe a higher percentage of APOE2 in their cases, compared to controls. Other studies failed to detect any significant differences in APOE genotypes between patients with kidney disease and controls (Feussner et al 1992, Guz et al 2000, Arikan et al 2007).…”
Section: Resultsmentioning
confidence: 90%
“…A total of 16 clinical studies [14,15,18-31] on ESRD and apoE variants published from 1992 and 2008 were identified, among which seven studies were form Asia [19,22-24,27,29,31], eight from Europe [14,15,20,21,25,26,28,30], and one from North America [18]. The literature review process was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In Hubacek et al’s study [13], patients in hemodialysis had higher frequency of ε2 than the control group (15.9% vs. 12.2%). However, Roussos et al [14] found patients with ESRD had no difference of ε2, ε3 and ε4 distribution compared with the control group. Feussner et al also failed to find the association between ε2 and ESRD [15].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due in part to the small sample size used in all but one study (70). Several studies (72)(73)(74) concluded that the ApoE4 isoform is associated with protection from type 2 DN in both white and Japanese individuals. Hsu et al (70) corroborated this finding, demonstrating that the frequency of the 4 allele is decreased in type 2 diabetes and chronic kidney disease and revealing association between the 2 allele and chronic kidney disease, a result that is consistent with several older studies of type 1 DN in white individuals (75,76) and one of type 2 DN in Japanese individuals (77).…”
Section: Additional Candidate Genes Of Interestmentioning
confidence: 88%